2013
DOI: 10.1016/j.bbamcr.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The CATS (FAM64A) protein is a substrate of the Kinase Interacting Stathmin (KIS)

Abstract: The CATS protein (also known as FAM64A and RCS1) was first identified as a novel CALM (PICALM) interactor that influences the subcellular localization of the leukemogenic fusion protein CALM/AF10. CATS is highly expressed in cancer cell lines in a cell cycle dependent manner and is induced by mitogens. CATS is considered a marker for proliferation, known to control the metaphase-to-anaphase transition during the cell division. Using CATS as a bait in a yeast two-hybrid screen we identified the Kinase Interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 42 publications
3
41
1
2
Order By: Relevance
“…The findings that expression of CATS (FAM64A) markedly increased the nuclear localization of CALM/AF10 [19] and that the murine Cats (Fam64A) transcripts were up-regulated in hematopoietic cells (B220 + lymphoid cells) transformed by CALM/AF10 in comparison to the same subpopulation from non-leukemic mice [10, 23], suggested that CATS (FAM64A) may play a role in CALM/AF10-mediated transformation. In agreement with that, CATS (FAM64A) functions as a transcriptional repressor [19] capable of antagonizing the transactivation activity of the leukemic fusion protein CALM/AF10 in a GAL4-based transactivation assay [24]. However, whether CATS (FAM64A) contributes to leukemogenesis remains to be determined.…”
Section: Introductionmentioning
confidence: 75%
“…The findings that expression of CATS (FAM64A) markedly increased the nuclear localization of CALM/AF10 [19] and that the murine Cats (Fam64A) transcripts were up-regulated in hematopoietic cells (B220 + lymphoid cells) transformed by CALM/AF10 in comparison to the same subpopulation from non-leukemic mice [10, 23], suggested that CATS (FAM64A) may play a role in CALM/AF10-mediated transformation. In agreement with that, CATS (FAM64A) functions as a transcriptional repressor [19] capable of antagonizing the transactivation activity of the leukemic fusion protein CALM/AF10 in a GAL4-based transactivation assay [24]. However, whether CATS (FAM64A) contributes to leukemogenesis remains to be determined.…”
Section: Introductionmentioning
confidence: 75%
“…According to its primary functions in mitosis (27), we speculate that CENPA influences survival in cancer by promoting chromosomal segregation, kinetochore association and genomic instability (28). FAM64A is a relatively new molecule, only a few reports exist on its involvement with ovarian cancer cell cycle and proliferation (29), therefore specific mechanisms and pathways on this molecule merit investigation. As for BUB1 and CCNB2, though the relationships with breast cancer has been reported (30,31), their role in TNBC still needs to be further addressed.…”
Section: Discussionmentioning
confidence: 97%
“…FAM64A is the substrate of the kinase-interacting stathmin (KIS or UHMK1), a serine/threonine protein kinase that promotes cell cycle progression through G1 by phosphorylation of the cyclin-dependent kinase inhibitor 1B (p27 Kip1 ) (29). Since AURKB and BUB1 are also serine/ threonine kinases, we doubt whether FAM64A is a substrate of AURKB or BUB1.…”
Section: Discussionmentioning
confidence: 99%
“…We suggested a possible role of UHMK1-PIMREG interaction in PICALM/MTT10 mediated leukemogenesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since then it has been described to interact with a range of proteins, such as peptidylglycine α -amidating monooxygenase (PAM) [2]; cyclin dependent kinase inhibitor (CDKI) p27 KIP1 [3]; splicing factors SF1 [4] and SF3b155 [5]; components of the neuronal RNA granules NonO, KIF3A and eEF1A [6]; proliferation marker PIMREG [7]; and RNA-binding proteins CPEB1, CPEB2 and CPEB3 [8], shedding light on different functions of UHMK1 in diverse cellular processes.…”
Section: Introductionmentioning
confidence: 99%